2018
DOI: 10.24869/psyd.2018.142
|View full text |Cite
|
Sign up to set email alerts
|

On the Addictive Power of Gabapentinoids: A Mini-Review

Abstract: The gabapentinoids gabapentin and pregabalin have been related to addiction citing pharmacovigilance data, some case presentations and increasing reports mainly from methadone maintenance treatment programs or emergency medicine. Most of these reports were based on patients with another current or previous substance use disorder (SUD). According to the ICD-10 dependence criteria, physical dependence (withdrawal symptoms, tolerance) was reported most frequently alongside regular use of gabapentinoids. Far less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
2
36
0
3
Order By: Relevance
“…Non-prescribed PGB was found in 14% of the MTT patients. The data on PGB obtained here aligned with those of other studies conducted on patients with past or present histories of misuse or abuse of other substances (30,32,38,(43)(44)(45)(46). A survey of MTT and buprenorphine patients in Georgia (47) revealed PGB misuse in 8.2% of the 506 participants.…”
Section: Pregabalin Abuse In the Cohortsupporting
confidence: 81%
See 1 more Smart Citation
“…Non-prescribed PGB was found in 14% of the MTT patients. The data on PGB obtained here aligned with those of other studies conducted on patients with past or present histories of misuse or abuse of other substances (30,32,38,(43)(44)(45)(46). A survey of MTT and buprenorphine patients in Georgia (47) revealed PGB misuse in 8.2% of the 506 participants.…”
Section: Pregabalin Abuse In the Cohortsupporting
confidence: 81%
“…It has been suggested that since PGB is easily accessible, it can be an alternative drug choice when opioids or other drugs of such kind are difficult to obtain and because PGB produces only few adverse effects. Some studies have attributed the relatively higher rates of PGB misuse among opioid users to pain mismanagement and opioid withdrawal symptoms (14,32,33). Overall, a similar pattern is seen with other medications (e.g.…”
Section: Pregabalin Abuse Potentialmentioning
confidence: 81%
“…Both gabapentinoids bind to the calcium channel, reducing the release of excitatory molecules. At therapeutic dosages, they are thought to possess GABA-mimetic properties, which may be behind the 'liking' (euphoric/relaxing high), but causing only limited rewarding ('wanting'), dopaminergic-related, properties (Berridge and Robinson, 2016;Bonnet and Scherbaum, 2017;Bonnet et al, 2018). A range of experiences may be associated with gabapentinoid highdosage abuse, including euphoria, improved sociability, opiate-like sedation, entactogenic feelings/dissociation, and psychedelic effects (Schifano et al, 2015).…”
Section: Prescription and Otc Drugsmentioning
confidence: 99%
“…The drug should be gradually tapered 1. Abrupt discontinuation may lead to withdrawal effects such as agitation, dysphoria, and fatigue 24. Reducing the dose by 50 to 100 mg/day each week for pregabalin and a maximum 300 mg/day each week for gabapentin is likely to be safe 25…”
Section: How Are They Given and Monitored?mentioning
confidence: 99%